(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The tax system, like any other system, as a set of elements and parts that complement each other and are interrelated and interact to achieve specific goals, and is a natural reflection of the economic, social and political conditions prevailing in society, and therefore the objectives of tax policy formulated in line with the objectives of economic policy in general, which means that any change in economic policy clearly affects fiscal policy measures and fiscal policy in particular. The problem of searching for the impact of foreign direct investment in the Iraqi tax system was focused on the study the of foreign direct investment and therole played in developing and improving the economic reality and its implications for the Iraqi tax system, based on the statistical tool, To explain the factors of foreign direct investment in the Iraqi tax system, as well as the use of the questionnaire as a tool to collect data, for the purpose of standing on the views and proposals of specialists working in the field of taxation and investment. The research reached conclusions, the most important of which is related to the procedures resulting from the tax reform, which can be adapted to the Iraqi tax system and in the line with the trends seeking to attract and activate the role of foreign direct investment in the Iraqi economy.The research recommended directing part of the inflows of investmentinto Iraq towards the untapped natural resources through multi-national companies because of its enormous material, human and technical potential, and directing part of these resources in the important infrastructure sectors that contribute to creating an attractive investment environment foreign investment. And improving the standard of living of individuals.